Nahuel Moreno a Livio Maitan - Nahuel Moreno (My University, 1966)
Documento de Nahuel Moreno sobre la crisis China dirigido a Livio Maitan.
Keywords: Cuarta Internacional; Maitan, Livio; China; Moreno, Nahuel